Florentine Normative Values for Physical Fitness in Adolescents Aged 14–15 Years - Mascherini, Gabriele; Buglione, Niccolò; Ciani, Virginia; Tirinnanzi, Franco; Bini, Vittorio; Levi Micheli, Matteo (Healthcare (Basel), 2022)
Physical fitness during youth is linked to the health of today’s young people and future adults. Therefore, fitness evaluation can direct any physical exercise interventions and verify improvements. The study aims to provide normative values of the physical fitness of the Florentine adolescent population. This cross-sectional study enrolled 1915 subjects aged 14 and 15 from the first and second high school classes. Tests were performed to assess cardiovascular endurance, upper and lower limb strength, running speed and agility, and lower limb muscle flexibility. Sex and age-related percentiles were elaborated. The study included 1028 subjects in the first class (aged 14.3 ± 0.8 years; 54.5% females) and 887 in the second class (aged 15.3 ± 0.7 years; 53.4% females). Males showed higher values than females except for flexibility. Furthermore, both genders show increased results in transitioning from the first to the second class, except for muscle flexibility and running speed. The percentiles of the present study provide normative values of the physical fitness of the 14–15-year-old Florentine adolescent population. These results, characterized by a sociocultural specificity linked to the territory from which they were collected, can contribute to the assessment and improvement of the physical status of young people, promoting current and future health.